Tindak Pidana Penyalahgunaan Narkotika Jenis Psikotropika yang Dilakukan Anggota TNI (Putusan No.80-K/PM I-02/AD/VII/2018) - Mulyadi Mulyadi; Thurva Naziha Visar; Habibie Rahman Sinaga; Baeyhaki Ekaputra Hamidi (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The Indonesian National Armed Forces (TNI) is part of society and protectors specially prepared to carry out the duties and defense of the country. In addition, the Indonesian National Army (TNI) is limited by laws and military regulations, so all actions undertaken must be based on applicable laws and regulations. To carry out specific duties and obligations, the Indonesian National Army (TNI) is educated and trained to comply with orders or decisions and carry them out appropriately and efficiently. The increase in the illicit circulation of narcotics in the territory of Indonesia is due to the lack of strictness or the lightness of the punishments imposed on dealers and users or the development of narcotics abuse and illicit trafficking not only in the general public but also in the military community, both as manufacturers, dealers and users. The illicit circulation of narcotics within the military is currently very concerning for the discipline and future of the Indonesian National Armed Forces (TNI) because it will lead to dependence on its users and hinder the implementation of its primary duties, damage the physical and mental health of military members who use narcotics, and the Criminal Code will be enforced. The Military Criminal Law, especially regarding the imposition of a sentence, but if the act is not regulated in the Criminal Procedure Code, another law that regulates it will apply. This study aims to find out the factors that cause narcotics abuse by military members and to analyze the judge's decision regarding the criminal act of narcotics abuse by members of the TNI. This study uses a normative juridical approach and is descriptive by using legal sources in the form of secondary data, in this case, bibliographical data. Data collection techniques are carried out using decision studies and searches of related documents, laws, literature, etc. The study results showed that the Military Prosecutor in the trial brought the defendant along with his identity data, and the defendant confirmed that the identity was his so that there was no wrong subject.